1990
DOI: 10.1016/s0022-5193(05)80374-1
|View full text |Cite
|
Sign up to set email alerts
|

Localized memories in idiotypic networks

Abstract: The present paper investigates conditions under which immunological memory can be maintained by stimulatory idiotypic network interactions. The paper was motivated by the work of (De Boer & Hogeweg, 1989b, Bull. math. Biol. 51, 381-408.) which claimed that idiotypic memory is not possible because of percolation within the network.Here we reinvestigate the issue of percolation using both the previous model and a simpler one (Weisbuch, 1990, J. theor. Biol. 143, 507-522.) that allows analytic analysis. We foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
57
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 19 publications
4
57
1
Order By: Relevance
“…The equilibrium fields of the idiotypic network models are typically located in the rising and the falling part of the bell-shaped function (Weisbuch et al, 1990;De Boer et al, 1992a, 1993a. Here we develop a rule of thumb for understanding the equilibria.…”
Section: Idiotypic Networkmentioning
confidence: 99%
“…The equilibrium fields of the idiotypic network models are typically located in the rising and the falling part of the bell-shaped function (Weisbuch et al, 1990;De Boer et al, 1992a, 1993a. Here we develop a rule of thumb for understanding the equilibria.…”
Section: Idiotypic Networkmentioning
confidence: 99%
“…The new model has the same five steady states as we previously described (De Boer, 1988;De Boer and Nogeweg, 1989a;Weisbuch et al, 1990;De Boer et al, 1993a). Three of the steady states are stable and we called them virgin, immune and suppressed.…”
Section: Idiotypic Networkmentioning
confidence: 99%
“…We have shown that in a network with a Cayley tree topology memory can remain localized, i.e. need not percolate (Weisbuch et al, 1990;Anderson et al, 1993) This result, however, is not robust because percolation is prevalent in Cayley trees with different affinities assigned to different branches and in trees whose topology is slightly modified by the addition of short odd loops (Neumann and Weisbuch, 1992a, b;Boutet de Monvel and Martin, 1995).…”
mentioning
confidence: 99%
See 2 more Smart Citations